Uji Efektivitas Air Perasan Daun Jeruk Limau Kuit ( Citrus hystrix ) Sebagai Insektisida Nabati Terhadap Mortalitas Kutu Rambut Pediculus humanus capitis Secara In Vitro - Pusvita, Nidha; Thuraidah, Anny; Rifqoh, Rifqoh; Rakhmina, Dinna (Jaringan Laboratorium Medis, 2022)
Lemongrass leaves are a typical plant of South Kalimantan which contain anti-insecticide, namely secondary metabolites such as alkaloids, saponins, tannins, steroids and triterpenoids. Pediculosis is a disease caused by a tick infection which is still neglected and becomes a health problem. One way to get rid of head lice is to use natural ingredients that contain anti-insecticide substances. This study aims to examine the possibility of using natural ingredients in lime leaves as vegetable insecticides against head lice mortality. The research method used is experimental, with a research design that is a post-test only control group, which measures and compares the mortality variable of Pediculus humanus capitis after being treated with lime leaf juice with concentrations of 10%, 30%, 60%, 100% during 1, 6, 12 and 24 hours and compared them with the negative control group with aquadest and the positive control with pemethrin. The sample of this study was lime leaf extract which was extracted by the method of squeezing using water. From the results of the study obtained the highest percentage of death at 12 and 24 hours with 100% mortality at a concentration of 100%. Based on the results of statistical tests using mortality observation data, the LC99 values were obtained within 1 hour (197.678%), 6 hours (126.055%), 12 hours (89.847%), and 24 hours (60.758%). Based on the results of the analysis of the data obtained, it can be concluded that there is effectiveness of lime leaf juice (Citrus hystrix) on the mortality of head lice (Pediculus humanus capitis) in vitro. Then the juice of lime leaves can be used as an alternative to getting rid of head lice with natural ingredients.